Епіграфи в Кулішевому романі “Чорна рада” (текстологічний аспект) - Федорук, О. (Слово і Час, 2018)
У статті проаналізовано епіграфи в тексті російського роману “Чорна рада”, їх функціонування
в ньому від початку створення до публікації 1857 р. Через епіграфи автор уводив російський текст
у силове поле українськості, водночас вони слугували своєрідним коментарем: письменник
пропонував подивитися на текст під певним ракурсом, наголошував або відтіняв якусь ідею,
тему, проблему. Вони кореспондували з текстом, і не тільки з російським, а й з українським,
відлунювали в ньому прямими цитаціями, алюзіями і грою смислів. Прив'язані до тексту того
розділу, якого стосуються, вони дають читачеві уявлення про майбутній розвиток дії або, навпаки,
є “універсальні” щодо змісту. The article analyzes the epigraphs in the Russian novel “The Black Council”, i. e. in which manners
they functioned from the beginning of its creation to the publishing in 1857. Kulish presents the Russian
text in the sphere of the Ukrainian identity with the help of epigraphs. At the same time they could be
considered as a commentary: the writer suggests looking at the content under the specific point of
view, he emphasizes some idea, topic, or problem. They correspond not only with the Russian text but
also with the Ukrainian, and echoing by the quotations, allusions, and game of symbols in it. Linked
to the text of the related sections, they illustrate an idea of the future development of the action or, in
contrary, give a “versatile” vision as regards the content.
Epigraphs could be related not only to a separate section, but also to several subsequent. They
separate these sections into some structural unit-cycle, amplify and particularize the dominant of the
theme of this cycle.
Besides functioning of the dialogue with the text and ‒ through the text ‒ with the reader, some
epigraphs obtained a more specific feature. They were addressed to different persons from the milieu
of Kulish’s friends whom he referred to in epigraphs in different manners.
Epigraphs to the sections of Kulish’s novel were taken from folkloric, historical, or literary sources.
The manuscript created in the exile contains epigraphs from Shakespeare’s drama (in the Russian
translation by Nikolai Ketcher) and the Russian poems of Aleksandr Pushkin or Ivan Dmitriev. The
author refused to use such sort of quotations in the future and built a strategy with regard to the
“Ukrainianization” of the epigraphs. Consequently, he followed such ideas up to the final version of
the novel. В статье проанализированы эпиграфы к русской версии
романа “Черная рада”, их функционирование в тексте от
начала создания до публикации в 1857 г. Посредством
эпиграфов автор вводил русский текст в силовое поле
украинскости, и одновременно они были своеобразным
комментарием: писатель предлагал посмотреть на текст в
определенным ракурсе, акцентировал или оттенял какую-
либо идею, тему, проблему. Они корреспондировали с
текстом, и не только с российским, но и с украинским,
отдавались в нем прямыми цитациями, аллюзиями и
игрой смыслов. Привязанные к тексту “своего” раздела,
они дают читателю представление о будущем развитии
действия или, наоборот, являются “универсальными” по
отношению к содержанию.